Managing intellectual property for competitive advantage in South African banks - Sibanda, Makhosazana Melissa (My University, 2017)
ABSTRACT South Africa has a well-developed banking system, which compares favourably with those of industrialized countries. The banking sector is very concentrated, but remains very competitive and continues to diversify its products and broaden its services. The financial service sector is not traditionally considered an IP-generating industry, however it is knowledge intensive and thus one of the fastest-growing industries in IP registration and IP commercialization. As a major economic asset, IP and its management and protection are the cornerstones of corporate strategy. IP is relevant to strategy since it is a component of intellectual capital, which is in turn an element of a firm’s core capabilities. IP is defined as a product originating from creativity of the human mind, which generates marketable value and comprises mostly of patents, trademarks, trade secrets and copyrights. IP is a legal asset that can be procured, traded, mortgaged, licensed, exchanged or gifted just like all other types of property. It supports revenue streams, establishes barriers to competition, and is closely linked to a firm’s perceived value to stakeholders such as investors and partners. This study establishes the existence of IP management systems within South African banks using qualitative research techniques, and uncovers the extent IP is used to gain a competitive advantage. The study uses data collected through semistructured interviews with representatives of eight respondents all of whom are attorneys who deal with IP issues both within the banks as well as externally. The data collected is analysed using thematic content analysis. The study concludes that IP plays several traditional roles such as conflict avoidance and strategic poisoning. However, IP assets are still not treated as strategic assets to the extent described in the literature. The study confirms that while the idea of integrated IP management is growing in the industry, its acceptance and use as an essential strategic tool has been relatively slow. This may negatively affect the industry’s ability to maximize the full benefits of IP especially in terms of creating alternative revenues, cutting costs and most importantly increasing the rate of innovation.
M.B.A. Thesis
Keywords: Banks and banking, Intellectual property -- South Africa, Technological innovations -- Management.